Low dose radiotherapy for COVID pneumonia: Irradiate to Eradicate – Will it be possible? Low dose radiotherapy for COVID pneumonia - Deokar, Kunal; Shadrach, Benhur Joel; Chawla, Gopal; Asfahan, Shahir; Dutt, Naveen; Niwas, Ram; Agarwal, Mehul; S, Aneesa Shahul (Acta Biomedica Atenei Parmensis, 2020)
.